2023
DOI: 10.3390/plants12061325
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potential of Microwave-Assisted Extraction Prepared Hydrolates from Different Salvia Species

Abstract: Salvia is a widely used herb that also contains essential oils and other valuable compounds. In this work, the hydrolates of five Salvia sp. were evaluated for their potential antimicrobial and antioxidant activity against four bacterial strains. The hydrolates were obtained from fresh leaves by microwave-assisted extraction. Chemical composition analysis by gas chromatography and mass spectrometry revealed that their major constituents were isopulegol (38.2–57.1%), 1,8-cineole (4.7–19.6%), and thujone (5.6–14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Regarding the comparison of data from the literature on the antioxidant activity researched by DPPH and ABTS tests of the same plant species and their hydrolates obtained by steam distillation as in our study, SM (Serbia), LO (Bulgaria, France), MO (Bulgaria), MP (Bulgaria), RO (France), SS (Slovak Republic), and LI and OV (Romania) hydrolates [38,56,63,65] are in the range of agreement with our results (Table 2). However, TV could not be appropriately compared with other TV hydrolates due to the different formats used in the studies [62,66,67] except for the excellent data agreement present for TV hydrolates from Romania [56].…”
Section: Antioxidative Properties Total Phenolics and Reducing Sugar ...mentioning
confidence: 95%
“…Regarding the comparison of data from the literature on the antioxidant activity researched by DPPH and ABTS tests of the same plant species and their hydrolates obtained by steam distillation as in our study, SM (Serbia), LO (Bulgaria, France), MO (Bulgaria), MP (Bulgaria), RO (France), SS (Slovak Republic), and LI and OV (Romania) hydrolates [38,56,63,65] are in the range of agreement with our results (Table 2). However, TV could not be appropriately compared with other TV hydrolates due to the different formats used in the studies [62,66,67] except for the excellent data agreement present for TV hydrolates from Romania [56].…”
Section: Antioxidative Properties Total Phenolics and Reducing Sugar ...mentioning
confidence: 95%
“…Furthermore, C. hystrix EO, has demonstrated inhibitory effect against various bacteria such as Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Staphylococcus epidermidis, and Proteus vulgaris [38]. The observed inhibitory effects of Citrus EOs against these bacteria are attributed to specific volatile components such as Dlimonene and isopulegol, which are believed to contribute significantly to their antimicrobial properties [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that Salvia sp. plants contain numerous flavonoids like apigenin 7-glucoside, 8-di-C-glucosyl apigenin, luteolin 7-glucoside, luteolin 7-diglucoside, and phenolic acids, which possess antioxidant and anti-inflammatory activities [171].…”
Section: Antidiabetic Activitymentioning
confidence: 99%